Relation of ear protector attenuation to noise spectra and methods for its determination - TRYNKOWSKA, Danuta; MICHALSKI, Ryszard (Archives of Acoustics, 1979)
454 spectra of industrial noise the sound level of which exceeded 90 dB (A), i.e. the maximum permissible values as established by the Polish Standard PN-70/03-02151 were analyzed. The real-ear attenuation for seven ear protectors was investigated and attenuation values for each of 454 noise spectra were calculated. An analysis of the attenuation of ear protectors as a function of the noise spectrum index Δ_CA was made and the regression curves for S_A = f(Δ_CA) were determined. Several methods for the determination of attenuation were given and a comparative analysis of the results was made. It follows from the analysis that the best method for determination of the attenuation uses the mean spectrum.